2002
DOI: 10.1046/j.1365-2052.2002.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

History and integrity of thoroughbred dam lines revealed in equine mtDNA variation

Abstract: Mitochondrial DNA (mtDNA) D-loop sequences (381 bp) from 100 thoroughbreds in 19 of the most common matrilineal female families were used to reconstruct a founder female population for the thoroughbred ( approximately 1650-1750 AD). Seventeen haplotypes were found to have contributed to the 19 female lineages. In order to place the reconstructed founder population in wider historical context, we examined, using both single strand conformation polymorphism and direct sequence analysis, variation in a 343 bp mtD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
103
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 9 publications
13
103
0
1
Order By: Relevance
“…In terms of conservation, the observed phylogenetic relationships should help to preserve the more original genetic groups and protect their genetic variability. At a species level, horses possess relatively high haplotype diversity in the D-loop region of mtDNA (Kim et al, 1999;Vilà et al, 2001;Hill et al, 2002;Royo et al, 2005). The mean number of pairwise differences observed among all haplotypes was estimated at 8.81 or 2.72%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of conservation, the observed phylogenetic relationships should help to preserve the more original genetic groups and protect their genetic variability. At a species level, horses possess relatively high haplotype diversity in the D-loop region of mtDNA (Kim et al, 1999;Vilà et al, 2001;Hill et al, 2002;Royo et al, 2005). The mean number of pairwise differences observed among all haplotypes was estimated at 8.81 or 2.72%.…”
Section: Discussionmentioning
confidence: 99%
“…Jansen et al (2002) reported extensive genetic diversity summarised in 93 different mtDNA types, grouped into 17 distinct phylogenetic clusters, and found that only a few of the phylogenetic clusters corresponded to groups of breeds or geographic areas. The examination of the horse population diversity at the mtDNA level has revealed a consistent absence of geographical structure (Hill et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). In this context, the results of mtDNA studies in horses, in which pedigree errors are usually identified (Hill et al, 2002;Kavar et al, 2002;Głażewska et al, 2007;Bower et al, 2013), are deserve attention. Of particular interest are the results presented by Hill et al (2000) and Bower et al (2013) on Thoroughbreds; these indicate that increased numbers of pedigree errors and haplotypes are identified when more detailed pedigree data are used.…”
Section: Discussionmentioning
confidence: 99%